Cation recognition by new diester- and diamide-calix[4]arenediquinones and a diamide-benzo-15-crown-5-calix[4]arene - Beer, P; Chen, Z; Gale, P; Heath, J; Knubley, R; Ogden, M; Drew, M (Kluwer Academic Publishers, 1994)
The synthesis, metal, ammonium and alkyl ammonium cation coordination chemistry and electrochemical recognition studies of new diester-and diamide-calix[4]arenediquinone receptors are described. In addition the synthesis and coordination properties of a novel diamide benzo-15-crown-5-calix[4]arene molecule is reported. © 1994 Kluwer Academic Publishers.